2020
DOI: 10.1101/2020.10.02.20204859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pooled Saliva Specimens for SARS-CoV-2 Testing

Abstract: We evaluated saliva (SAL) specimens for SARS-CoV-2 RT-PCR testing by comparison of 459 prospectively paired nasopharyngeal (NP) or mid-turbinate (MT) swabs from 449 individuals with the aim of using saliva for asymptomatic screening. Samples were collected in a drive-through car line for symptomatic individuals (N=380) and in the emergency department (ED) (N=69). The percent positive and negative agreement of saliva compared to nasopharyngeal swab were 81.1% (95% CI: 65.8% – 90.5%) and 99.8% (95% CI: 98.7% – 1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 30 publications
(76 reference statements)
2
21
0
1
Order By: Relevance
“…Overall, twenty-one studies had low risk of bias (63.6%) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 35 , 38 , 39 , 40 , 41 , 42 , 43 ], eleven raised some concerns (33.3%) [ 21 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 36 ] and one had high risk of bias (3.0%) [ 37 ] ( Figure 2 ) (fully detailed in Supplementary S3 , pp. 12).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, twenty-one studies had low risk of bias (63.6%) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 35 , 38 , 39 , 40 , 41 , 42 , 43 ], eleven raised some concerns (33.3%) [ 21 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 36 ] and one had high risk of bias (3.0%) [ 37 ] ( Figure 2 ) (fully detailed in Supplementary S3 , pp. 12).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, as a diagnostic specimen, "saliva" deserves a particular attention, and several considerations need to be taken into account. Firstly, most studies accounted for salivary samples circumscribed to the oral region (anterior to the throat) [ 12 , 13 , 15 , 20 , 22 , 26 , 30 , 33 , 34 , 35 , 37 , 38 , 39 , 40 , 42 ], while the remaining studies analyzed DTS/POS with or without pre-throat saliva [ 25 , 27 , 29 , 32 , 41 , 43 ]. This fact is very important as the salivary characteristics and the collection method differ, and the DTS/POS may contain samples other than the oropharyngeal region (naso-pharyngeal or laryngeal-pharyngeal) [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various pooling strategies have been developed since the beginning of the COVID-19 pandemic [ [4] , [5] , [6] , [7] , [8] ]. While the need for pooling is clear, the impact on sensitivity varies among studies and depending on the size of the pool and the platform and assay used.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that there were no differences in performance between symptomatic and asymptomatic patients and high viral loads could be detected in saliva of asymptomatic or pre-symptomatic patients, further supporting the potential use of saliva pool testing [ 3 ]. In their study, Barat et al evaluated pooled saliva testing in pools of five using two commercial assays (Panther Fusion and Roche Cobas 6800) [ 4 ]. The authors reported a sensitivity of at least 90% for all three methods with the Roche Cobas showing a sensitivity of 94% similar to results from our study with a 6 samples pool size.…”
Section: Discussionmentioning
confidence: 99%